Observation of two-mode squeezing in the microwave frequency domain - Bozyigit, Deniz; Lang, C.; Baur, Matthias; Steffen, Lars; Fink, J. M.; Filipp, Stefan; Wallraff, Andreas J; Eichler, Christopher (Physical Review Letters, 2011)
Continuous variable entanglement between two modes of a radiation field is usually studied at optical frequencies. Here we demonstrate experiments that show the entanglement between microwave photons of different energy in a broadband squeezed beam. We use a Josephson parametric amplifier to generate the two-mode correlated state and detect all four quadrature components simultaneously in a two-channel heterodyne setup using amplitude detectors. Analyzing two-dimensional phase space histograms for all possible pairs of quadratures allows us to determine the full covariance matrix, which is in good agreement with the one expected for a two-mode squeezed state. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-27